Deradicalization through Revitalization of Religious and Nationality Insights among Indonesian Students - Muhammad Turhan Yani; Yusuf Hanafi (Faculty of Education and Teacher Training, Institut Agama Islam Negeri Pekalongan, 2022)
Radicalism is part of an ideology that can grow and develop anywhere, including in colleges or universities. The study aimed to depict the phenomenon of radicalism among students by analyzing how radical influences could infiltrate students from the Islamic education lecturers' perspective. This study also examined lecturers' efforts to prevent radicalization in the campus environment. The data were collected through in-depth interviews conducted over three months. Results showed that although the campus continued to be reported by many studies as the